Public-private partnerships in urban redevelopment a comparative case study of Quezon City, Philippines, and Sao Paulo, Brazil - Rossitto, Carla Nadal (School of Urban and Regional Planning, University of the Philippines Diliman, 2016)
This study discussed Public-Private Partnerships (PPPs) as an implementation tool for urban redevelopment projects in developing countries. As these PPPs are dealing with the commercialization of land, the dialectic between land markets and inclusive cities is analyzed, with focus on the social-spatial dynamics resulting from such projects. Therefore, this study is developed under the research question How are Public-Private Partnerships in Urban Redevelopment Related to the Conflict Between Land Markets and Inclusive Cities?" The aim of the study is to provide significant inputs for the refinement of policies for future urban redevelopment projects, implemented through PPP, in the context of metropolitan regions in developing countries. Furthermore, it offers a comprehensive view of the impacts of PPP's implementation on the socio-spatial distribution of the cities. This would assist the local government on properly administrating PPPs as a land use planning instrument.This study conducted a qualitative research methodology approach, based on primary and secondary data. The research focused in two comparable case studies-the North triangle PPP in Quezon City, Philippines, and the Faria Lima PPP in Sao Paulo, Brazil - and analyzed the empirical concerns of the existing literature, considering the relationship of PPPs and the deeper purpose of land use planning as an instrument of social engineering as theoretical themes.For the purpose of this study, four units of analysis were delineated in order to frame the discussion on PPPs in urban redevelopment, and allow future replications for research in this topic. Specifically, they are : (1) The polycy framework addressing PPPs in urban redevelopment and its implication in land market and segregation issues; (2) The factors that contribute to the organization of PPPs' stakeholders; (3)The implementation scheme of the PPP projects; and (4)The impacts of the PPP project design and on the socio-spatial dynamics of the city.The findings demonstrate that a solid and well conceptualized policy framework towards inclusive cities, empowers the local government into negotiating with the private sector, avails the public participation on the PPP implementation scheme, and is key to overcome the conflict between land market and segregation. On the other hand, without strong spatial policy and in the absence of tools and resources for its implementation locally, local planning is especially exposed to, and driven by, the economic power of the existing land oligarchies, which often thrust forward their interests without regard for societal impacts.Nevertheless, in the context of developing countries, PPPs as technical instruments may be useful to contribute to the development of the urban space even from a social justice perspective. In fact, PPPs as an urban planning instrument can be positive or negative regarding the democratization of the urban space. As it is not on the technic of the instrument to be against the social interest, the progressive character of the PPPs relies upon its formulation on the municipal or national level. Above all, these partnerships are a political matter, and depend on the mobilized civil society to assure that its implementation will guarantee the interests of the majority; assuring the construction of inclusive cities.